Theory of Plates and Shells - Timoshenko S (Mcgraw Hill Book Company, 1959)
Preface, Notation, Introduction, Bending of Long Rectangular Plates to a Cylindrical Surface, Pure Bending of Plates, Symmetrical Bending of Circular Plates, Small Deflections of Laterally Loaded Plates, Simply Supported Rectangular Plates, Rectangular Plates with Various Edge Conditions, Continuous Rectangular Plates, Plates on Elastic Foundation, Plates of Various Shapes, Special and Approximate Methods in Theory of Plates, Bending of Anisotropic Plates, Bending of Plates under the Combined Action of Lateral Loads and Forces in the Middle Plane of the Plate, Large Deflections of Plates, Deformation of Shells without Bending, General Theory of Cylindrical Shells, Shells Having the Form of a Surface of Revolution and Loaded Symmetrically with Respect to their Axis, Name and Subject Index.